(untitled) (Journal of Interdisciplinary Insights, 2024)
This study evaluates the effectiveness of the Presentation-Assimilation-Discussion (PAD) teaching approach in enhancing student interest in practical courses at Weifang University of Science and Technology, Shou Guang, China. The PAD Class method, which emphasizes a balanced integration of teacher-led presentations, student self-assimilation, and group discussions, has gained attention for its potential to foster active learning and improve learning outcomes. A quantitative research design was employed, and data were collected via a structured questionnaire distributed online using the Wenjuanxin platform. The sample consisted of 200 students from four majors: Applied Electronic Technology, Computer Application Technology, Computer Network Technology, and Software Technology. Descriptive and inferential statistical analyses were conducted to assess changes in student interest levels pre- and post-implementation of the PAD method, as well as differences across majors. The findings indicate a significant increase in student interest across all majors post-implementation of the PAD method, suggesting its effectiveness in enhancing student engagement and enthusiasm for learning. The study provides valuable insights for educators and administrators seeking to improve educational outcomes through innovative teaching practices.